Research on the Innovative Path of Cultural and Creative Transformation of Tibetan Thangka Intangible Cultural Heritage - Wang, Lulu; Da, Wazhasang; Mohamed, Fauzi Naeim (Design Journal, 2025)
This study examines the innovative integration of Tibetan Thangka, a 1,300-year-old painting tradition and national intangible cultural heritage, with contemporary cultural and creative industries. The research aims to identify effective strategies for preserving Thangka's cultural essence while enhancing its market viability and social relevance in the digital age. Using a mixed-methods approach combining literature analysis, case studies of successful cultural transformations, and comparative evaluation of existing Thangka initiatives, this study develops a "Four Crosses" framework for cultural heritage innovation: cross-element integration (talent and capital collaboration), cross-platform integration (digital communication matrix), cross-industry integration (extending the "Thangka+" value chain), and cross-audience integration (targeted product design). Results demonstrate that successful transformation requires balancing traditional craftsmanship with contemporary design approaches, leveraging digital technologies for wider dissemination, creating immersive cultural experiences, and adapting cultural symbols for modern consumption while maintaining their philosophical integrity. The findings contribute to broader discussions on sustainable preservation of intangible cultural heritage in market economies.